Múltiplas faces femininas da tessitura literária de Inês Sabino - Silveira, Sinéia Maia Teles (2014)
This paper is about Inês Sabino s prose from the literary and gender s perspective. The corpus is composed by the books Contos e lapidações (1891) and Lutas do coração ([1898] 1999). The text discusses the author s process of identity construction, recognizing her as an ex-eccentric from the XIX century. The main purpose of this study is the analysis of the rhetoric s resources that cooperate to lead Sabino s prose to a more refined literary level, as the narrator, the implicit author, the use of metatextualities, metafictions and dialogues with the reader. She also uses elements that categorize her production as an example of woman s Bildungsroman (PINTO, 1990). The analysis ratifies the formulated hypothesis, revealing, in the narrative construction, how the author breaks with the model of masculine romance from that age and initiates a reflection about the autonomy of woman s character in her society, what is called the women s Bildungsroman.